Gerodietіс meat products technoljgy enriched with calcium - Peshuk, Ludmila; Galenko, Oleg; Korshnivska, О. (My University, 2014)
This paper presented a method of enrichment of boiled sausages calcium and calcium-additive role in the development Gerontologic diet of meat products.
Keywords: технологія; геродієтичний продукт; м’ясо; технология; геродиетичний продукт; мясо; technology; gerodietic products; meat; кафедра технології м’яса і м’ясних продуктів